Students’ Responses to Educational Game-Based Learning Media in Mathematics Instruction at Madrasah Ibtidaiyah (Journal Of Islamic Education And Pesantren, 2025)
Mathematics learning in Madrasah Ibtidaiyah (MI) continues to face challenges related to students’ low interest and active participation, which are partly caused by the limited use of varied learning media. This study aims to analyze students’ responses to the use of educational game-based learning media in mathematics instruction at the Madrasah Ibtidaiyah level. The study employed a quantitative descriptive approach using an evaluative survey design. The research subjects consisted of 24 fifth-grade students who participated in mathematics learning on the topic of perimeter and area of plane figures using an educational game-based medium adapted from a ludo game. Data were collected through a Likert-scale student response questionnaire and analyzed using descriptive quantitative techniques. The results indicate that the educational game-based learning media received a very positive response from students, with a response percentage of 92.1%, categorized as very good. The positive responses were reflected in aspects of media attractiveness, ease of use, clarity of material presentation, and the usefulness of the media in supporting students’ understanding of mathematical concepts. These findings suggest that educational game-based learning media have a high level of acceptability and potential to create a more engaging, enjoyable, and meaningful mathematics learning experience for Madrasah Ibtidaiyah students.